2008
DOI: 10.1016/j.asoc.2007.07.007
|View full text |Cite
|
Sign up to set email alerts
|

AISIID: An artificial immune system for interesting information discovery on the web

Abstract: There exist numerous systems for mining the web in search of relevant information but few exist for the discovery of interesting information. The discovery of interesting information is an advance on basic text mining in that it aims to identify text that is novel, unexpected or surprising to a user, whilst still being relevant. This article investigates the use of Artificial Immune Systems (AIS) applied to discovery of interesting information. AIS are thought to confer the adaptability and learning required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…(7) and mutation number can be calculated by Eq. (8). The mutation principle is the same as that of mc in a) (clone and mutation of mc …”
Section: A Scln-airs Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…(7) and mutation number can be calculated by Eq. (8). The mutation principle is the same as that of mc in a) (clone and mutation of mc …”
Section: A Scln-airs Modelmentioning
confidence: 98%
“…As an bionic method inspired by human immune system, artificial Immune System (AIS), has been widely used in control engineering [6] , pattern recognition [7] , information security [8] , fault diagnosis [9] , etc. AIS exhibits great capability on information processing and data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Spam detection was another area where AIS is be applied ( [12], [13]). Other than that, AIS was also used to search for interesting web pages ( [14]) and to classify medical documents ( [15], [16]). …”
Section: B Using Ais To Classify Textmentioning
confidence: 99%
“…For that reason, it made the increasing use of effective applications like web mining system as a tool to find relevant information on the Internet by the Internet user. The reason why they chose to use these tools was because these tools have information about the processing techniques which is efficient in filtering and finding relevant information [2]. In this research, we have found a machine learning technique known as Artificial Immune System (AIS) that has the paradigm to evolve and learn.…”
Section: Introductionmentioning
confidence: 99%